A POLYNOMIALIN C++ DATA ABSTRACT TYPE - Ruiz Lizama, Edgar (2004)
This article presents a program in C++ which defines a class of polynomial name in order to implement a data abstract type (TAD), a polynomial through a class that performs polynomials arithmetic with operations such as addition, the product of a constant by a polynomial, the product of a monomial by a polynomial and a polynomial derived. The program code is presented, and its details, features and limitations are discussed. Implementation is done in the Dev C++ 4.1 compilator; a GNU compilator with GPL licence.